Leadership in an Organization from the Perspective of Leaders and Employees - Maria Wanda Kopertyńska; Natalia Dernowska- Żaczyk; Katarzyna Stefaniuk-Żygadło (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu)
Aim: The purpose of the research was to determine how leadership is perceived in the organization and what challenges leaders face.